1994
DOI: 10.3354/meps104139
|View full text |Cite
|
Sign up to set email alerts
|

Temporal fluctuations of two Mediterranean salp populations from 1967 to 1990. Analysis of the influence of environmental variables using a Markov chain model

Abstract: The weekly abundances of the sexual phase (aggregate zoold) of 2 salp populatlons (tunlcates Thaha democratlca and Salpa fuslform~s) were determined from 1967 to 1990 at a fixed statlon in the coastal waters of the Western Mediterranean, using a discrete scale of abundance For both specles the abundance tlme senes shows the occasional developn~ent of blooms of aggregate zoolds Several hydrologlcal and meteorological variables were recorded concormtantly, and thelr Influence on the occurrence of blooms was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
2
42
0
2
Order By: Relevance
“…However, they are generally underestimated because standard sampling devices used for mesozooplankton damage or destroy their fragile bodies and are therefore inappropriate for their quantitative estimation. The pelagic filter-feeding tunicates, and especially the salps, are known to occur periodically in dense swarms, sometimes with outbreaks lasting for days or weeks (Bone, 1998;Ménard et al, 1994). It seems, however, that salps form smaller swarms in the MS than in other oceans, which could be related to the oligotrophic nature of this sea (Andersen, 1998).…”
Section: Other Groupsmentioning
confidence: 94%
“…However, they are generally underestimated because standard sampling devices used for mesozooplankton damage or destroy their fragile bodies and are therefore inappropriate for their quantitative estimation. The pelagic filter-feeding tunicates, and especially the salps, are known to occur periodically in dense swarms, sometimes with outbreaks lasting for days or weeks (Bone, 1998;Ménard et al, 1994). It seems, however, that salps form smaller swarms in the MS than in other oceans, which could be related to the oligotrophic nature of this sea (Andersen, 1998).…”
Section: Other Groupsmentioning
confidence: 94%
“…3) suggested that autumn, at the end of the wet season and during the transition period between southwest and northeast monsoons, might be a more favorable season for most thaliacean species to live and reproduce in this region. However, Ménard et al (1994) found that Thalia democratica and Salpa fusiformis were more abundant from April to June in the Mediterranean Sea, and proposed that this might be a result of the spring phytoplankton bloom. Ménard et al (1997) reported that doliolids in the bay of the northwestern Mediterranean Sea were abundant mostly from July to December and seemed to be temperature-related, while Gibson & Paffenhöfer (2000) further revealed that the feeding and growth rates of doliolids are a function of food concentration and temperature.…”
Section: Day-night Vertical Distribution and Abundancementioning
confidence: 99%
“…Some thaliaceans are found in dense populations at high latitudes (Bathmann 1988, Huntley et al 1989, or in productive shelf and coastal waters (Wiebe et al 1979, Zeldis et al 1995, particularly during the spring phytoplankton bloom (Gorsky et al 1991, Ménard et al 1994, 1997. Some thaliaceans are known to perform extensive diel vertical migration (DVM); for instance, Salpa aspera migrates over 800 m in the slope water of the western North Atlantic (Wiebe et al 1979), while Pyrosoma atlanticum migrates from 90 to 760 m with different colony sizes in the Ligurian Sea (Andersen & Sardou 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal patterns in the occurrence of abundance peaks of salps have also been observed in other areas (Ménard et al, 1994;Licandro, ibañez & Etienne, 2006;Deibel & Paffenhöfer, 2009). Tunicates could be a seasonal food resource for sea turtles and other filter-feeding vertebrates if their abundance is directly linked to recurring oceanographic patterns.…”
Section: Discussionmentioning
confidence: 66%
“…Unfortunately, organisms could not be identified to species due to sample deterioration caused by prolonged storage. Tunicate abundances were classified according to the following categories: 1) 1-3 ind/m 3 , 2) 4-17 ind/m 3 , 3) 18-80 ind/m 3 , 4) 80-350 ind/ m 3 , and 5) 350-1 500 ind/m 3 (Frontier, 1969;Ménard, Dallot, Thomas & Braconnot, 1994).…”
Section: Study Areamentioning
confidence: 99%